Abnormal purinergic signaling contributes to development of renal cysts in autosomal dominant polycystic kidney disease - Veniamin Ivanov; Andrew Wu; Letizia Crocetti; Ze Meng; Puja Shrestha-Maskey; Tang-Dong Liao; Indra Adrianto; Gabriella Guerrini; Pablo A. Ortiz; Tengis S. Pavlov (Purinergic Signalling, 2026)

Early Cretaceous freshwater bivalves from northeastern Brazil: Insights into the evolutionary history of South American freshwater mussels - Victor R. Silva; Vitor B. Guerrini; Filipe G. Varejão; Rafael C. Silva; Katie Collins; Ismar S. Carvalho; Simon Schneider; Marcello G. Simões (Cretaceous Research, 2026)

Long-term biodegradable mulch films application in agricultural fields: effects on soil functionality and microplastic generation - M. Mazzon; C. Edo; S. Guerrini; P. Gioacchini; J. Cupi; P. Malena; R. Rosal; C. Marzadori (Journal of Environmental Management, 2026)

Shake-table testing of a stone masonry building aggregate: overview of blind prediction study - I. Tomić; A. Penna; M. DeJong; C. Butenweg; A. A. Correia; P. X. Candeias; I. Senaldi; G. Guerrini; D. Malomo; B. Wilding; D. Pettinga; M. Spanenburg; et al. (Bulletin of Earthquake Engineering, 2024)
City centres of Europe are often composed of unreinforced masonry structural aggregates, whose seismic response is challenging to predict. To advance the state of the art on the seismic response of these aggregates, the Adjacent Interacting Masonry Structures (AIMS) subproject from Horizon 2020 project Seismology and Earthquake Engineering Research Infrastructure Alliance for Europe (SERA) provides shake-table test data of a two-unit, double-leaf stone masonry aggregate subjected to two horizontal components of dynamic excitation. A blind prediction was organized with participants from academia and industry to test modelling approaches and assumptions and to learn about the extent of uncertainty in modelling for such masonry aggregates. The participants were provided with the full set of material and geometrical data, construction details and original seismic input and asked to predict prior to the test the expected seismic response in terms of damage mechanisms, base-shear forces, and roof displacements. The modelling approaches used differ significantly in the level of detail and the modelling assumptions. This paper provides an overview of the adopted modelling approaches and their subsequent predictions. It further discusses the range of assumptions made when modelling masonry walls, floors and connections, and aims at discovering how the common solutions regarding modelling masonry in general, and masonry aggregates in particular, affect the results. The results are evaluated both in terms of damage mechanisms, base shear forces, displacements and interface openings in both directions, and then compared with the experimental results. The modelling approaches featuring Discrete Element Method (DEM) led to the best predictions in terms of displacements, while a submission using rigid block limit analysis led to the best prediction in terms of damage mechanisms. Large coefficients of variation of predicted displacements and general underestimation of displacements in comparison with experimental results, except for DEM models, highlight the need for further consensus building on suitable modelling assumptions for such masonry aggregates.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Current recommendations for cancer surveillance in Gorlin syndrome: a report from the SIOPE host genome working group (SIOPE HGWG) - L. Guerrini-Rousseau; M. J. Smith; C. P. Kratz; B. Doergeloh; S. Hirsch; S. M. J. Hopman; M. Jorgensen; M. Kuhlen; O. Michaeli; T. Milde; V. Ridola; A. Russo; et al. (Familial Cancer, 2021)
Gorlin syndrome (MIM 109,400), a cancer predisposition syndrome related to a constitutional pathogenic variation (PV) of a gene in the Sonic Hedgehog pathway ( PTCH1 or SUFU) , is associated with a broad spectrum of benign and malignant tumors. Basal cell carcinomas (BCC), odontogenic keratocysts and medulloblastomas are the main tumor types encountered, but meningiomas, ovarian or cardiac fibromas and sarcomas have also been described. The clinical features and tumor risks are different depending on the causative gene. Due to the rarity of this condition, there is little data on phenotype-genotype correlations. This report summarizes genotype-based recommendations for screening patients with PTCH1 and SUFU -related Gorlin syndrome, discussed during a workshop of the Host Genome Working Group of the European branch of the International Society of Pediatric Oncology (SIOPE HGWG) held in January 2020. In order to allow early detection of BCC, dermatologic examination should start at age 10 in PTCH1 , and at age 20 in SUFU PV carriers. Odontogenic keratocyst screening, based on odontologic examination, should begin at age 2 with annual orthopantogram beginning around age 8 for PTCH1 PV carriers only. For medulloblastomas, repeated brain MRI from birth to 5 years should be proposed for SUFU PV carriers only. Brain MRI for meningiomas and pelvic ultrasound for ovarian fibromas should be offered to both PTCH1 and SUFU PV carriers. Follow-up of patients treated with radiotherapy should be prolonged and thorough because of the risk of secondary malignancies. Prospective evaluation of evidence of the effectiveness of these surveillance recommendations is required.

[d-Pen(p- t BuBzl)5]NPS, a novel ligand for the neuropeptide S receptor: structure activity and pharmacological studies - C. Ruzza; L. del Zoppo; D. Malfacini; M. Pela’; C. Trapella; P. Grieco; S. Salvadori; G. Calo’; R. Guerrini (Medicinal Chemistry Research, 2014)

Desensitisation of native and recombinant human urotensin-II receptors - Madura S. Batuwangala; Girolamo Calo; Remo Guerrini; Leong L. Ng; John McDonald; David G. Lambert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Antidepressant-like effects of the nociceptin/orphanin FQ receptor antagonist UFP-101: new evidence from rats and mice - E. C. Gavioli; C. W. Vaughan; G. Marzola; R. Guerrini; V. A. Mitchell; S. Zucchini; T. C. M. De Lima; G. A. Rae; S. Salvadori; D. Regoli; G. Calo’ (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Pharmacology of [Tyr1]nociceptin analogs: receptor binding and bioassay studies - K. Varani; A. Rizzi; G. Calo; R. Bigoni; G. Toth; R. Guerrini; S. Gessi; S. Salvadori; P.A. Borea; D. Regoli (Naunyn-Schmiedeberg's Archives of Pharmacology, 1999)

Clozapine metabolism rate as a possible index of drug-induced granulocytopenia - M. C. Mauri; R. Rudelli; S. Bravin; S. Gianetti; E. Giuliani; A. Guerrini; R. Orlandi; G. Invernizzi (Psychopharmacology, 1998)